Travels of Karel Čapek. On the Role of the Imaginative Variation in the Letters from Various Parts of Europe - Skibska, Anna Maria (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2017)
In the article, I take into con sid era tion a series of Karel Čapek’s letters, which deliver a charming and cheerful evidence of his travel ex pe ri ences resulted from his visits in various parts of Europe. In order to unveil the Czech writer’s origi nal ity regarding the poetics of trave logue, I refer to a number of figures, which are to organize his peculiar epis to lary idiom. Čapek’s style is, therefore, de ter mined by irony which turns out to be streaked with sub se quent rhe tori cal devices such as litotes, cor rec tion, and self- correction linked with el lip ti cal presence of apo sio pe sis. What is more, the Czech writer invests in the so-called variant manner of writing, due to which his letters instead of the common travel knowledge provides the reader with de scrip - tions con cern ing details: from the tra di tional point of view, they might be perceived as mean ing less facts, however, in Čapek letters they are trans formed into in di vid ual, unique, and ex cep tional events, which are to remain in the reader’s con scious ness.
Keywords: travelogue; irony; litotes; correction; imaginative variation